2020
DOI: 10.1186/s13023-020-1303-2
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygous IFT140 variants in two Polish families with Sensenbrenner syndrome and early onset end-stage renal disease

Abstract: Background: Sensenbrenner syndrome, which is also known as cranioectodermal dysplasia (CED), is a rare, autosomal recessive ciliary chondrodysplasia characterized by a variety of clinical features including a distinctive craniofacial appearance as well as skeletal, ectodermal, liver and renal anomalies. Progressive renal disease can be life-threatening in this condition. CED is a genetically heterogeneous disorder. Currently, variants in any of six genes (IFT122, WDR35, IFT140, IFT43, IFT52 and WDR19) have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The deletion variant in IFT140 r.2765_2768 has previously been reported as a likely pathogenic variant in ClinVar (VCV000863072.3) in a patient with retinal dystrophy, as well as, a patient with MZSDS. The duplication variant in IFT140 NC_000016.9:g.1568118(NM_014714.4):c (4182 + 99)_(3558)dup is absent from ClinVar, but has been detected in two Polish skeletal ciliopathy patients and in eight families reported by Geoffroy ( Geoffroy et al, 2018 ; Walczak-Sztulpa et al, 2020 ). These include six families (seven patients) diagnosed with MZSDS, one patient with JATD and one affected individual with features of CED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion variant in IFT140 r.2765_2768 has previously been reported as a likely pathogenic variant in ClinVar (VCV000863072.3) in a patient with retinal dystrophy, as well as, a patient with MZSDS. The duplication variant in IFT140 NC_000016.9:g.1568118(NM_014714.4):c (4182 + 99)_(3558)dup is absent from ClinVar, but has been detected in two Polish skeletal ciliopathy patients and in eight families reported by Geoffroy ( Geoffroy et al, 2018 ; Walczak-Sztulpa et al, 2020 ). These include six families (seven patients) diagnosed with MZSDS, one patient with JATD and one affected individual with features of CED.…”
Section: Resultsmentioning
confidence: 99%
“…-Congenital CMV infection -Epilepsy (absence attacks) from the age of 13 years, treated with Valproate -MRI -normal a -IFT140-related MZSDS, phenotype based on literature (Perrault et al, 2012;Schmidts et al, 2013;Geoffroy et al, 2018;Oud et al, 2018); b -IFT140-related CED, phenotype based on literature (Bayat et al, 2017;Walczak-Sztulpa et al, 2020); c -CED, phenotype based on literature, excluding IFT140 (Gilissen et al, 2010;Walczak-Sztulpa et al, 2010;Arts et al, 2011;Bredrup et al, 2011); CT, computed tomography; EEG, electroencephalography; ID, intellectual disability; Mat, maternally inherited variant; MRI, magnetic resonance imaging; NA, data not available; Pat, paternally inherited variant; WG, weeks of gestation. + feature present;-feature absent; *presence, number of renal cysts, revealed by repeated ultrasonography not seen at baseline, has increased over time of follow-up; # unclear.…”
mentioning
confidence: 99%
“…Using a cilium dual reporter-expressing mouse model, we found that a small group of hepatocytes were ciliated. Among ciliopathies, liver cysts and fibrosis are common pathological changes, suggesting that primary cilia are essential to the normal function of the liver [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…We applied qPCR to determine the 17p13.3 locus dosage and narrow down its genomic coordinates using SYBR dye-based master mix (SYBR Green PCR Master Mix; ThermoFisher Scientific). Reactions ran on the Viia7 cycler as described previously [ 25 ]. In short, we applied the comparative 2 −ΔΔCT method using control DNA as a calibrator.…”
Section: Methodsmentioning
confidence: 99%